Hydrolysis of Canola Oil Under Subcritical Conditions for Biodiesel Synthesis - Mello, B.T.F.; Zempulski, D.A.; Cardozo-Filho, L.; Silva, C. (Asian Journal of Chemistry, 2016)
This study presents the synthesis of canola hydrolyzate for the production of biodiesel using subcritical water. The reactions were conducted in continuous mode evaluating the effects of temperature, pressure and the oil to water mass ratio at different residence times. A pressure increase from 10 to 15 MPa, favoured the production of higher levels of free fatty acids. The free fatty acid formation was directly proportional to the temperature increase in the experimental range evaluated and high yields were obtained at low residence times. The use of larger amounts of water in the reaction mixture provided the greatest formation of free fatty acids; however, the use of oil to water mass ratios above 1:2 had no significant effects (p > 0.05) on the free fatty acids content, possibly because the reaction reached equilibrium conditions. Free fatty acids yields of about 90 % for an oil to water mass ratio of 1:2, 15 MPa, 305 °C and 9.5 min of reaction are reported.